Long-Term Trends of Clinical Distribution and Resistance Patterns of Klebsiella pneumoniae Infections from 2014 to 2022: A Retrospective Study - Na Wang; Minghua Zhan; Teng Wang; Jinlu Liu; Caiqing Li; Baoliang Li; Xuying Han; Huiying Li; Shuting Liu; Jing Cao; et al. (Research Perspectives of Microbiology and Biotechnology Vol. 7, 2024)
Background: Klebsiella pneumoniae (KP) is a common opportunistic pathogen in hospitalized patients, often causing pneumonia, urinary tract infection, and bacteremia. Gastrointestinal carriage is a risk factor for nosocomial infections. Purpose: The purpose was to determine the pattern of Klebsiella pneumoniae (KP) infection and drug resistance through long-term and large sample-size statistical analysis and to provide epidemiological data for the treatment, prevention, and control of multidrug-resistant bacterial infection in the hospital. Patients and Methods: In this study, 5442 strains of Klebsiella pneumoniae were collected from the First Affiliated Hospital of Hebei North University of China from January 1, 2014, to June 30, 2022. Strains were identified using the BD PhoenixTM100 system, minimal inhibitory concentrations of antibiotics were determined by the broth method, and data were statistically analyzed using WHONET 5.6 and SPSS27.0. Results: The study found that the isolation rate of KP from Enterobacteriaceae (26.2%, 4547/17358) in our hospital showed an increasing annual trend, ranking second only to Escherichia coli. Carbapenem-resistant KP (CRKP) accounted for the highest proportion of carbapenem-resistant Enterobacteriaceae (72.2%, 431/597), showing an upward trend. Infected patients had a male-to-female ratio of approximately 2:1 and were mainly >60 years of age (66.2%), with intensive care units being the most commonly distributed department. Sputum was the most common specimen type (74.0%). Compared with spring and summer, autumn and winter were the main epidemic seasons for KP and extended-spectrum \(β\)-lactamase KP (ESBL-KP). The resistance rate of KP to common antibiotics was low, but all showed an increasing trend each year. ESBL-KP was >90% resistant to piperacillin, amoxicillin/clavulanic acid, and cefotaxime and less resistant to other common antibiotics, but showed an increasing trend in resistance to most antibiotics. CRKP resistance to common antibiotics was high, with resistance rates >90%, excluding amikacin (64.1%), gentamicin (87.4%), cotrimoxazole (44.3%), chloramphenicol (13.6%), and tetracycline (30.5%). Additionally, the detection rate of CRKP showed a rapidly increasing trend from 2014 to 2018, and then a slowly decreasing trend from 2018 to 2022, while ESBL-KP showed an initially increasing trend, followed by another decrease, then an increase. Conclusion: KP in our hospital mainly caused pulmonary infection in older men, which occurred frequently in autumn and winter, and the isolation and drug resistance rates showed an increasing trend. Age over 70 years, admission to the intensive care unit, and urinary tract infection were found to be the risk factors for CRKP and ESBL-KP resistance. It is recommended that in the face of the high transmission and mortality of CRE, the WHO should actively strengthen international collaborations to study and develop new antibiotics against third-generation cephalosporins and CRE to jointly curb the spread of multi-drug resistance.